Energy Yield Assessment from Ocean Currents in the Insular Shelf of Cozumel Island - Juan Carlos Alcérreca-Huerta; Job Immanuel Encarnacion; Stephanie Ordoñez-Sánchez; Mariana Callejas-Jiménez; Gabriel Gallegos Diez Barroso; Matthew Allmark; Ismael Mariño-Tapia; Rodolfo Silva Casarín; Tim O’Doherty; Cameron Johnstone; Laura Carrillo (Journal of Marine Science and Engineering, 2019)
Marine renewables represent a promising and innovative alternative source for satisfying the energy demands of growing populations while reducing the consumption of fossil fuels. Most technological advancements and energy yield assessments have focused on promoting the use of kinetic energy from tidal streams with flow velocities higher than 2.0 m s−1. However, slower-moving flows from ocean currents are recently explored due to their nearly continuous and unidirectional seasonal flows. In this study, the potential of the Yucatan Current was analysed at nearshore sites over the insular shelf of Cozumel Island in the Mexican Caribbean. Field measurements were undertaken using a vessel-mounted Acoustic Doppler Current Profiler (ADCP) to analyse the spatial distribution of flow velocities, along with Conductivity-temperature-depth (CTD) profiles as well as data gathering of bathymetry and water elevations. Northward directed flow velocities were identified, with increasing velocities just before the end of the strait of the Cozumel Channel, where average velocities in the region of 0.88–1.04 m s−1 were recorded. An estimation of power delivery using horizontal axis turbines was undertaken with Blade Element Momentum theory. It was estimated that nearly 3.2 MW could be supplied to Cozumel Island, amounting to about 10% of its electricity consumption.